FIGURATIVE LANGUAGE IN THE STATLER BROTHERS’ SELECTED SONG LYRICS FOR LITERATURE TEACHING - Ghanaro, Mohammad; Hidayat, Nur; Sodiq, Jafar (FKIP - Universitas Tanjungpura, 2022)
Figurative language and its meaning is always been a part of literary work. This study aims to identify the types of figurative language used in The Statler Brothers’ selected song lyrics, to find the meaning of the figurative language used in the selected song lyrics, and to elaborate the contribution of the study for literature teaching. The research design of this study is qualitative research. In data collection of the study, the writer has analyzed The Statler Brothers’ selected songs namely “Bed of Rose’s”, “New York City”, “Flowers on the Wall”. “Elizabeth”. “Do You Know You Are My Sunshine”, “Pictures”, and “We Got Paid by Cash”. The study results the dominant types of figurative language used in the songs is hyperbole as classified by using Kennedy’s theory. The songwriter uses hyperbole to deliver the idea and feeling effectively which is suitable to Kempson’s theory. The figurative language in The Statler Brothers’ songs can be used as alternative learning material to literature teaching. The writer suggests that the students should learn more about the meaning and the nature of words and sentences. This study is expected to be alternative reference to the next researcher to explain more about figurative language.